Tuberculosis Disease Incidents in Bitung City, North Sulawesi Province 2022-2024 - Azyuyun Azyuyun; Sri Muliani (Journal of Health Science and Pharmacy, 2025)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. The disease primarily affects the lungs, although it may also involve other organs of the human body. Common clinical manifestations include a persistent cough lasting more than two weeks, weight loss, fever, and fatigue. Despite ongoing control efforts, TB remains a major public health concern in many regions of Indonesia. Objective: This study aims to describe the incidence and distribution of tuberculosis cases in Bitung City, North Sulawesi Province, during the period 2022–2024. Methods: A quantitative descriptive approach was employed to analyze the distribution of TB cases in Bitung City. Secondary data were obtained from the Central Statistics Agency of North Sulawesi and reports published by the North Sulawesi Provincial Health Office. Data analysis focused on identifying temporal patterns and year-to-year differences in TB incidence and treatment outcomes. Results: The findings indicate a declining trend in reported TB cases over the study period, which may reflect the effectiveness of public health interventions such as expanded early case detection, increased community awareness of TB symptoms, and strengthened health service networks targeting high-risk populations. However, the TB treatment success rate showed a decrease, from 88.1% in 2022 to 76% in 2024. This decline suggests ongoing challenges related to treatment adherence, potential delays in diagnosis, and limitations in patient monitoring and follow-up. Conclusion: The distribution of tuberculosis cases in Bitung City from 2022 to 2024 demonstrates notable changes. While the reduction in TB incidence suggests progress in promotive and preventive efforts, the declining treatment success rate highlights the need to strengthen comprehensive treatment management, improve patient adherence, and enhance continuity of care to achieve sustainable TB control outcomes.